Endodermal sinus tumor diagnosed in pregnancy: a case report. Issue 4 (1st July 2007) - Robova, H.; Rob, L.; Hrehorcak, M.; Zoban, P.; Prusa, R.
Abstract : Pure endodermal sinus tumor (EST) of the ovary is an uncommon germ cell tumor characterized by rapid growth. Its occurrence during pregnancy is extremely rare. The case of a 34-year-old woman with EST stage IC diagnosed in the 22nd week of gestation is presented. She received four cycles of cisplatin monotherapy during pregnancy. Further, three cycles of combination chemotherapy (cisplatin, bleomycin, and etoposide) were administered. Twenty-eight months posttreatment the patient was in complete remission with good health. A healthy female infant was delivered by cesarean section in the 35th week of pregnancy. The child showed normal laboratory, pediatric, and neurologic examination at the time of discharge from hospital and during the first and second years of her life. We conclude that the prognosis of EST is very good if patient receives adjuvant therapy. Cisplatin monotherapy seems to be effective and safe during pregnancy